1998
DOI: 10.1145/279361.279372
|View full text |Cite
|
Sign up to set email alerts
|

Multi-level texture caching for 3D graphics hardware

Abstract: Traditional graphics hardware architectures implement what we call the push architecture for texture mapping. Local memory is dedicated to the accelerator for fast local retrieval of texture during rasterization, and the application is responsible for managing this memory. The push architecture has a bandwidth advantage, but disadvantages of limited texture capacity, escalation of accelerator memory requirements (and therefore cost), and poor memory utilization. The push architecture also requires the programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It was found that although it has been suggested that caches are critically inefficient for video data (several media processor chips dispense with data caches entirely), there was sufficient reuse of values for caching to significantly reduce the raw required memory bandwidth. [17], [10], and [39] study the usefulness of caching the textures used in 3D rendering. A texture cache with a capacity as small as 16 KB has been found to reduce the required memory bandwidth three to fifteen times over a non-cached design and exhibit miss ratios around 1% [17].…”
Section: Related Workmentioning
confidence: 99%
“…It was found that although it has been suggested that caches are critically inefficient for video data (several media processor chips dispense with data caches entirely), there was sufficient reuse of values for caching to significantly reduce the raw required memory bandwidth. [17], [10], and [39] study the usefulness of caching the textures used in 3D rendering. A texture cache with a capacity as small as 16 KB has been found to reduce the required memory bandwidth three to fifteen times over a non-cached design and exhibit miss ratios around 1% [17].…”
Section: Related Workmentioning
confidence: 99%
“…Finally, it can be combined with a hardware rendering pipeline, functioning in that context like a mipmap texture cache. We believe that many observations made in previous texture caching papers [7,2,10] could be applied in our algorithm, which has similar (but not identical) characteristics. For example, both texture caching and our algorithm perform better when the access pattern exhibits good coherence.…”
Section: Discussionmentioning
confidence: 88%
“…The bilinear, trilinear, and anisotropic filters applied to texture stored in the form of a MIP map pyramid [48] offer significant amount of spatial and temporal locality. This observation has inspired a large number of studies on texture cache architectures including single-level texture caches [13], two-level texture caches [7], texture caches in parallel renderers [16,47], prefetching into texture caches with deep FIFO structures [1,17,26,45], victim caching [6], four-dimensional and six-dimensional tiling of texture data [13], and customized DRAM architectures for fast texture access [8,43]. A texture cache architecture with on-the-fly decompression of texture data from a second level compressed texture cache has also been explored [45].…”
Section: Memory Management In 3d Renderingmentioning
confidence: 99%